(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2025)
This article addresses the relevance of environmental communication in raising awareness and educating tourists about the responsible disposal of micro-waste on the beaches of Santos. It emphasizes the influence of media on environmental perception, underscoring the need for effective strategies to deal with this often overlooked type of waste. To achieve these goals, documentary analysis, content analysis, exploratory research, and a single-case study were employed. The research highlights the lack of information targeted at tourists in the analyzed materials, indicating the absence of a specific focus by the government on this issue. The adoption of innovative tools, such as Artificial Intelligence and Augmented Reality, is recommended to positively impact tourists during their stay. Despite inherent limitations, the study contributes by proposing strategies for reducing micro-waste, emphasizing the need for future research to assess the effectiveness of these approaches in the context of sustainable tourism.